2016
DOI: 10.1111/ajco.12447
|View full text |Cite
|
Sign up to set email alerts
|

Radiation recall pneumonitis induced by erlotinib after palliative thoracic radiotherapy for lung cancer: Case report and literature review

Abstract: Radiation lung injury usually develops 1-6 months after cessation of radiation therapy to the lung. Acute change in the previously irradiated lung after administration of antineoplastic agent is known as radiation recall pneumonitis. Erlotinib is a reversible epidemal growth factor receptor tyrosine kinase inhibitor, which is effective for patients with advanced lung cancer with epidermal growth factor receptor mutations. Here we report a rare case of radiation recall pneumonitis following treatment with erlot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 25 publications
0
15
0
1
Order By: Relevance
“…RRP induced by chemotherapy is diagnosed on the basis of previous thoracic radiotherapy, radiographic abnormalities, and the clinical presentation. Symptoms appear within days or weeks after administration of the antitumor agent, and RRP can develop several weeks to months after radiotherapy completion . Antitumor agents that can cause RRP include anthracyclines, taxanes, gefitinib, erlotinib, gemcitabine, and sunitinib .…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…RRP induced by chemotherapy is diagnosed on the basis of previous thoracic radiotherapy, radiographic abnormalities, and the clinical presentation. Symptoms appear within days or weeks after administration of the antitumor agent, and RRP can develop several weeks to months after radiotherapy completion . Antitumor agents that can cause RRP include anthracyclines, taxanes, gefitinib, erlotinib, gemcitabine, and sunitinib .…”
Section: Discussionmentioning
confidence: 94%
“…Symptoms appear within days or weeks after administration of the antitumor agent, and RRP can develop several weeks to months after radiotherapy completion. [2][3][4][5]13 Antitumor agents that can cause RRP include anthracyclines, taxanes, gefitinib, erlotinib, gemcitabine, and sunitinib. [5][6][7][8][9] For this patient, (i) no imaging and clinical symptoms were observed for 9 months after radiotherapy (radiation pneumonitis typically occurs within 6 months after radiotherapy); (ii) acute interstitial pneumonia began 3 days after nivolumab administration; (iii) the damaged area was consistent with the radiation field; (iv) the patient exhibited improvement upon PSL treatment after discontinuation of nivolumab; and (v) the patient had not been treated with other suspect drugs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been suggested that lung tumors are becoming more common in younger patients (29). Currently, the most efficient methods of treating lung cancer are surgery, radiotherapy, chemotherapy and immunotherapy (30). However, a majority (>67%) of newly diagnosed patients are diagnosed at an advanced stage of cancer (31).…”
Section: Discussionmentioning
confidence: 99%